INGLIS HÁM QARAQALPAQ NAQÍL-MAQALLARÍNDA MIYNET ISKERLIGINIŃ KONCEPTUALLÍQ MAYDANÍ HÁM TIPOLOGIYASI - Kutlimuratova, Aysuliw Baxitovna (SCIENCE and SOCIETY, 2026)
The article analyzes the conceptual field and typology of the concept of labor activity in proverbs in English and Karakalpak languages, which are not typologically and genealogically similar. This concept has a universal character in both languages, and it has been determined that the formation of its typology is based on the national-cultural views of both peoples. English proverbs prioritize individual achievements and the valuation of time in terms of labor activity, while Karakalpak proverbs reveal the meaning of the concept in relation to social development and nature.